A new species of Rhyacophila (Trichoptera: Rhyacophilidae) and new records of Trichoptera from Asia - Kiss, Ottó (Zootaxa, 2016)
A new species of the Rhyacophila scissa Group (Trichoptera, Rhyacophilidae), Rhyacophila huesunensis n. sp. from Taiwan (Republic of China), is described and illustrated with drawings of the genitalia. Also, new records of eight caddisfly species from Asia are presented.